Hierarchy, networks, or markets: how does the EU shape environmental policy adoptions within and beyond its borders? - Knill, Christoph; Tosun, Jale (Journal of European public policy, 2009)
In this study we scrutinize the strength of the European Union's ‘external governance’ in the area of environmental policy. We explore whether accession candidates and third countries adopted European environmental legislation along with the member states. In doing so, we focus on Community laws that limit nitrogen oxides in the emissions into the air from large combustion plants, and introduce the European ecolabel scheme and environmental impact assessments. Our analysis reveals that hierarchical governance is the most significant and robust determinant of policy adoption. Additionally, our results lend some support to the relevance of network governance, indicating that this mode could become more effective at greater length.
Gesehen am 22.11.2023